Efektivitas E-Modul Pembelajaran Instalasi Tenaga Listrik Berbasis Edutaiment - Rino Suwirno; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2022)
This research was conducted at SMK N 1 Padang in class XII TITL on the subject of electrical power installation. Student learning outcomes are still low resulting in learning objectives have not been achieved. Based on observations of low student scores caused by the module used by the teacher is still classified as conventional so that students' enthusiasm for learning decreases. Therefore, this research was conducted so that the modules applied to students can be varied so that teachers can find out which modules are suitable for students, in this study using the application of e-modules to determine the effectiveness of learning on student learning outcomes. This research uses experimental research which is categorized into a quasi-experimental design research with Posttest-Only Control Design. The sample of this research is class XII TITL SMK Negeri 1 Padang in the academic year 2022/2023. Data collection in this study used a test instrument in the form of posttest objective questions. The selection of experimental and control classes used simple random sampling technique. The data obtained were analyzed using classical completeness and Effect Size. From the calculation, the classical completeness value exceeds the minimum value, this shows that the use of e-modules is effective in improving student learning outcomes. While the Effect Size value is obtained with a large category. Effect size shows the magnitude of the effect of a treatment on two variables, namely the experimental class and control class, the result of the experimental class value is higher than the control class so it can be concluded that the use of e-modules is effective in improving student learning outcomes. effect size is the most important unit of research results.